If men were angels, no government would be necessary : two essays on the effects of regulations on banking sector valuation and risk - Balani, Henry (University of Wisconsin--Whitewater, 2017)
The banking sector plays a central role in economic development by providing financial services for a country’s growth and stability. When banks seek to maximize profits, they may engage in non-compliant behavior that negatively impacts market growth and stability. Regulatory oversight is therefore common in this sector. Regulations can lead to improved transparency and reporting, however, can also be a burden due to complexity, increasing costs of compliance with varying impacts on stock valuations of banks. While the intent is to correct behavior for non-compliance, we continue to see ongoing negative banking events post-2000, evidenced by the London Interbank Offered Rate (LIBOR) and subprime mortgage crisis, as well as the abuse of the banking system by money launderers, raising the issue that regulations are not effective in changing bank behavior. Essay 1 seeks to examine the effectiveness of regulatory signals by measuring valuation and risk impact based on enforcement actions on banks. I found that overall, bank returns are positively impacted by the announcement of enforcement actions as the fines are less harsh and not as large as expected. When testing bank-specific attributes, I found that larger banks were more negatively impacted by penalties while larger size fines had a positive effect on valuation. There was no significant impact of risk on bank returns on the day of the fine. However, banks that experienced the greatest increase in risk had the higher returns six months after the fine. When testing the impact of the fine on competitor banks, I found that there was no significant impact, suggesting no spillover effect. When testing competitor bank characteristics, I found that the fined banks with higher returns impacted competitor banks positively. Larger competitive banks were more positively impacted, while competitive banks with higher market risks reacted negatively. Similar to the fined banks, competitor banks that experienced the greatest increase in risk had higher returns six months after the fine. Overall, the results indicated that enforcement actions are not effective and do not send a strong signal to the banking industry to correct behavior. Essay 2 attempts to assess the impact of the introduction of the fourth European Union (EU) Anti-Money Laundering Directive (4AMLD) on European banks by examining whether eight milestone dates impacted stock valuation and risk. I found that valuations and risk were positively impacted when a time series analysis was conducted over the milestone event dates. An examination of bank-specific characteristics based on a cross sectional regression revealed that riskier, larger banks have higher returns as a result of the introduction of the 4AMLD. Also, banks with a higher return on assets see more positive returns. However, banks that rely more on non-traditional income streams have lower returns. In EU countries where Gross Domestic Product (GDP) per capita is higher, banks experience more positive returns than in poorer countries. Similarly, banks in less corrupt countries see more positive returns. Banks in countries with lower levels of governance, where governments are less effective and have less stable political systems and regulatory oversight, experience positive returns as a result of the introduction of the 4AMLD. The results show that with the introduction of the 4AMLD, banks gained greater clarity and guidance related to identifying and reporting on money laundering transactions, allowing banks in countries with lower levels of governance to comply effectively based on the clarity of requirements and the framework of the 4AMLD.
This file was last viewed in Microsoft Edge.
Keywords: Banks and banking--State supervision; Money laundering--Prevention; Banks and banking--Corrupt practices--Prevention; Banks and banking--Valuation; Fines (Penalties)